INDUSTRIAL ECOLOGY AS THE PRECURSOR GRAND THEORIES TO CIRCULAR ECONOMY: BIBLIOGRAPHIC MAPPING OF 112 LITERATURE - Dania Sitadewi; Gatot Yudoko; Liane Okdinawati (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2021)
Abstract: Environmental degradation require business to rethink their way of doing business. Industrial Ecology (IE) is a paradigm change that allows a cyclical resource-use in which Circular Economy (CE) rethink and recycle the waste generated into a industrial input, thereby reducing environmental burden. Industrial Ecology (IE) is one of the most referenced grand theories for Circular Economy (CE). This research aims to map IE to CE bibliographically to identify research trends, prominent researchers, and countries with the most publication. This research's methodology is bibliographic mapping of 112 articles using VOSviewer in three steps: data acquisition, data processing, and visual output. This research has identified three research findings. The first finding is the identification of five clusters that correspond with the current research trend. The second finding is identifying Geng Y., Lai K.H., and Zhu Q. as the leading researchers for CE and IE. The third finding is China is the leading country for CE and IE research. The implication is China aiming to transform its industry into environmentally more sustainable. Future research topic venue can incorporate other grand theories to expand the theoretical and practical focus of CE.